THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION - Astuti , Sherly Dwi; Prayekti, Prayekti; Kusuma , Nala Tri (International Conference on Humanity Education and Society (ICHES), 2024)
Job satisfaction is a satisfactory work result in an organization, several literatures can increase job satisfaction such as promotions, wages, work environment, supervision and relationships with coworkers. The purpose of this research is to determine the influence of transformational leadership, work motivation, and work environment on employee job satisfaction. This quantitative research methodology uses saturated sampling techniques and data collection through questionnaires distributed to 62 employees of CV Cahaya Setia Mulia Yogyakarta, while data processing uses SPSS version 22. The research results show that transformational leadership and the work environment do not have a significant influence. has an effect on employee job satisfaction, while work motivation has a significant effect on employee job satisfaction.